Economic impediments to successful seismic retrofitting decisions. Issue 5 (4th November 2014) - Egbelakin, Temitope; Wilkinson, Suzanne; Ingham, Jason
Abstract : Purpose: – The purpose of this paper is to examine why building owners are often reluctant to adopt adequate mitigation measures despite the vulnerability of their buildings to earthquake disasters, by exploring the economic-related barriers to earthquake mitigation decisions. Design/methodology/approach: – A case study research method was adopted and interviews chosen as the method of data collection. Findings: – Critical economic-related impediments that inhibited seismic retrofitting of earthquake-prone buildings were revealed in this study. Economic-related barriers identified include perception about financial involvement in retrofitting, property market conditions, high insurance premiums and deductibles, and the high cost of retrofitting. The availability of financial incentives such as low interest loans, tax deductibles, the implementation of a risk-based insurance premium scale and promoting increased knowledge and awareness of seismic risks and mitigation measures in the property market place are likely to address the economic-related challenges faced by property owners when undertaking seismic retrofitting projects. The provision of financial incentives specifically for seismic retrofitting should be introduced in policy-implementation programme tailored to local governments' level of risks exposure and available resources. Practical implications: – The recommendations provided in this study suggest strategies and answers to questions aimed at understanding the types of incentives that city councils and environmental hazard managers should focus on in their attempt to ensure that property owners actively participate in earthquake risk mitigation. Originality/value: – This paper adopts a holistic perspective for investigating earthquake risk mitigation by examining the opinions of the different stakeholders involved in seismic retrofit decisions.